2019
DOI: 10.1016/j.dental.2019.08.101
|View full text |Cite
|
Sign up to set email alerts
|

Pre-heating effects on extrusion force, stickiness and packability of resin-based composite

Abstract: Objectives. To measure temperature effects on stickiness and packability of representative resin-based composites and the effect of pre-heating time on pre-cure properties of Viscalor, including extrusion force. Methods. Five resin-based composites (RBC) and an additional RBC, Viscalor, used with a Caps Warmer (VOCO, Germany) were studied. The extrusion force (N) and extruded mass (g) were measured from Viscalor compules heated in T3 mode for 30 s (T3-30s) and 3 min (T3-3min). For stickiness and packability me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
0
16
1
8
Order By: Relevance
“…In the literature there is not enough information regarding the effect of preheating on the viscosity of bulk fill composites. A study indirectly assessed the effect of preheating on the viscosity of VCB by evaluating the extrusion force and found that the extrusion force for the preheated VCB capsule (68°C for 3 min) was 66.49±14.16 N whereas it was 153.62±1.56 N for the unheated VCB capsule 37) . Another study evaluated the viscosity of FBF at different temperatures, and found that viscosity of FBF at 25°C was 0.05±0.00 kPa s and 0.03±0.01 kPa s at 37°C; which was a 48.7% change in viscosity 38) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there is not enough information regarding the effect of preheating on the viscosity of bulk fill composites. A study indirectly assessed the effect of preheating on the viscosity of VCB by evaluating the extrusion force and found that the extrusion force for the preheated VCB capsule (68°C for 3 min) was 66.49±14.16 N whereas it was 153.62±1.56 N for the unheated VCB capsule 37) . Another study evaluated the viscosity of FBF at different temperatures, and found that viscosity of FBF at 25°C was 0.05±0.00 kPa s and 0.03±0.01 kPa s at 37°C; which was a 48.7% change in viscosity 38) .…”
Section: Discussionmentioning
confidence: 99%
“…Em concordância com esse estudo, Yang, Silikas & Watts (2019), avaliaram que o uso de resina pré-aquecida conseguiu uma melhor adaptação marginal devido à termoplasticidade das resinas compostas, ocasionando uma menor força de extrusão, uma melhor aderência e nem afeta no grau de conversão dos monômeros. Entretanto, o pré-aquecimento de resinas fluidas como no caso da Bulk-fill flow (Filtek), apresentou uma serie de defeitos principalmente no grau de conversão dos monômeros, porém quando se pré-aqueceu as resinas compostas como a Z250 (filtek) à 55ºC houve um aumento significativo na conversão destes monômeros (Lempel et al, 2019).…”
Section: Discussionunclassified
“…No entanto, esses agentes duplos contêm mais amina terciária; quando esses componentes oxidam, ocorre uma alteração significativa da cor do agente de cimentação, resultando em estética comprometida do procedimento restaurador. Assim, o uso de agentes de cura fotopolimerizantes deve ser considerado nos casos em que a estética é fundamental, desde que restrita a procedimentos adesivos de restaurações mais finas, como laminados cerâmicos e facetas (Azer et al, 2011;Yang, Silikas & Watts, 2019).…”
Section: Introductionunclassified
“…Clinicamente, foi observado que a aplicação de calor em resinas restauradoras antes da fotoativação podia reduzir sua viscosidade e facilitar a sua extrusão do interior da embalagem, além de melhorar a adaptação nas paredes do preparo cavitário e reduzir a microinfiltração marginal (2,4,6). Alguns estudos, inclusive, sugerem o uso de resinas restauradoras pré-aquecidas em substituição das resinas fluidas como base de adaptação do material restaurador em preparos cavitários de difícil acesso.…”
Section: Viscosidadeunclassified
“…Há alguns anos, estudos clínicos e laboratoriais analisam o pré-aquecimento das resinas restauradoras como uma forma prática e simples de otimizar algumas de suas características sem alterar a composição (2,3). O aumento da temperatura da resina antes de sua fotoativação é capaz de reduzir a sua viscosidade e assim facilitar a sua extrusão do interior da embalagem e melhorar a sua acomodação nas paredes do preparo cavitário (4)(5)(6). Além disto, com o pré-aquecimento, o grau de conversão das ligações duplas de carbono da resina pode aumentar e levar a formação de um polímero mecanicamente mais resistente e quimicamente mais estável (7)(8)(9).…”
Section: Introductionunclassified